Cloning and determination of biochemical properties of protective and broadly conserved vaccine antigens from the genome of extraintestinal pathogenic Escherichia coli into pET28a vector - Jamil Kheirvari Khezerloo; Zohreh Haghri; Mana Oloomi; Mohammad Reza Asadi Karam; Mehri Habibi (Islamic Azad University, 2017)
Urinary tract infections are one of the most common infectious diseases that lead to significant health problems in the world. Urinary tract infections are referred to any infection in any part of the renal system. Uropathogenic Escherichia coli, Proteus mirabilis, and Klebsiella are main organisms that are involved in these infections. After identifying same protective and conserved virulence sequences in these microorganisms with similarity upper than 80%, sequences of synthetic gene was provided by bioinformatics techniques and ordered from Thermo Fisher Scientific Company. PCR amplification of this gene was performed by specific primers designed for this purpose. Construction of gene was performed by overlap PCR. The synthetic gene was cloned into pET28a vector. Our gene was amplified in E. coli Top10 tested. To confirm cloning, three methods including colony PCR, digestion and sequencing were used. First, two techniques were performed using horizontal electrophoresis, and also the synthetic gene showed significant homology with the sequence (99% Identified) in sequencing. Sequencing of this gene showed that fusion was constructed correctly. Determination of biochemical properties such as 3D structure, Ramachandran and comparison of Non-redundant Set of PDB structure was done by bioinformatic software and had exact and expectable results. A large part of the health system in the world is occupied by a urinary tract infection and governments spend a huge amount of money for the treatment and recovery of patients with these infections. On the other hands, antibiotic resistance in the not-far future will be a disaster for medical societies. This is the most important reason for the emergence of vaccine production against urinary tract infections.